Magnetic nano material as well as preparation method and application thereof
By using the solid-phase microextracting materials prepared by using magnetic nanomaterials Fe3O4@rGO and Ni3 (HITP)4, the SLs isomers were successfully separated and measured using magnetic solid-phase microextraction technology, solving the problem of difficulty in separation and determination in the prior art, and achieving a high sensitivity and efficient analysis method.
Patent Information
- Application Number
- CN202411992742.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
It is difficult to efficiently separate and determine different cyperolide (SLs) isomers in the prior art.
The solid phase microextracting material prepared based on the reaction of magnetic nanomaterials Fe3O4@rGO and Ni3 (HITP)4 was used to separate and determine the SLs isomers by magnetic solid phase microextraction technology.
The efficient separation and determination of SLs chiral isomers was achieved, with the detection limit reaching 1.93-3.76pg/mL, and the recovery rate was 86.90-106.37%. The method was simple, fast and environmentally friendly.
Smart Images

Figure BDA0005223979110000051 
Figure BDA0005223979110000061 
Figure BDA0005223979110000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biochemistry, and specifically relates to a magnetic nano material and a preparation method and application thereof. Background Art
[0002] Strigolactone (SL) is a new type of plant hormone derived from carotenoids that significantly regulates plant growth and development. In 1966, SLs were first discovered from the root secretions of cotton (Gossypiumhirsutum L.), and it was determined that they have the function of inducing the germination of parasitic plants such as strigolactone and Orobanche. In 2008, a study found that SLs were synthesized in the roots and stems of rice and Arabidopsis. SLs were transported upward through the xylem or acted directly in the stems, inhibiting the tillering and branching process of the plant and negatively regulating the growth and development of the branch. At present, the difference in the activity of different SLs isomers has always been a hot topic of research. Umehara et al. used stereoisomers of 5-DS, ostandol, GR24, GR7, and GR5 to treat rice and Arabidopsis, and found that the 2'R isomer had stronger biological activity than the 2'S isomer in inhibiting the growth of tiller buds. Artuso et al. synthesized a series of monocotyl lactone analogs and clarified that their absolute configuration was related to their biological activity. They also found that analogs with R-configured butenolide moieties showed enhanced biological activity.
[0003] Therefore, a method that can effectively separate and determine different SLs isomers is urgently needed. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes to prepare a solid phase microextraction material based on magnetic nanomaterials.
[0005] The invention also provides a method for preparing the magnetic nanomaterial.
[0006] The invention also proposes the application of the magnetic nano material.
[0007] According to a first aspect of the present invention, a magnetic nanomaterial is provided. The magnetic nanomaterial is prepared by reacting Fe3O4@rGO and Ni3(HITP)4.
[0008] The magnetic nanomaterial is a material used for solid phase microextraction.
[0009] In some embodiments of the present invention, the mass ratio of Fe3O4@rGO to Ni3(HITP)4 is 1:1.5-2.5.
[0010] In some embodiments of the present invention, the Fe3O4@rGO is a Fe3O4@rGO dispersion, which is obtained by dispersing Fe3O4@rGO in a solvent.
[0011] In some embodiments of the present invention, the dispersion method uses ultrasound, and the ultrasound treatment time is 45-75 minutes.
[0012] In some embodiments of the present invention, the Ni3(HITP)4 is a Ni3(HITP)4 dispersion.
[0013] In some embodiments of the present invention, the reaction time is 25-45 min.
[0014] According to a second aspect of the present invention, a method for preparing the above-mentioned magnetic nanomaterial is proposed, and the preparation method comprises the following steps: preparing the magnetic nanomaterial by reacting Fe3O4@rGO and Ni3(HITP)4.
[0015] In some embodiments of the present invention, the Fe3O4@rGO is prepared by the following method: after reacting rGO and an iron-containing metal salt, an alkaline solution is added, and the mixture is treated at 75 to 85° C. for 1 to 3 hours to obtain Fe3O4@rGO.
[0016] In some embodiments of the present invention, the iron-containing metal salt includes ferric chloride and ferrous sulfate.
[0017] In some embodiments of the present invention, the mass ratio of the rGO to the iron-containing metal salt is (30-40):1.
[0018] In some embodiments of the present invention, the mass ratio of the rGO to the iron-containing metal salt is (32-38):1.
[0019] In some embodiments of the present invention, the reaction is carried out under the condition of introducing nitrogen, and the flow rate of the nitrogen is 30-50 mL / min.
[0020] In some embodiments of the present invention, the reaction further comprises a step of ultrasonic dispersion treatment, and the time of the ultrasonic dispersion treatment is 25-35 minutes.
[0021] In some embodiments of the present invention, the alkaline solution comprises an aqueous ammonia solution.
[0022] In some embodiments of the present invention, the mass fraction of the aqueous ammonia solution is 20% to 30%.
[0023] In some embodiments of the present invention, the 75-85°C condition is provided by heating in a water bath.
[0024] In some embodiments of the present invention, the step of cleaning the Fe3O4@rGO is further included, wherein the cleaning is performed using pure water and ethanol.
[0025] In some embodiments of the present invention, the step of drying the washed Fe3O4@rGO is further included, wherein the drying is performed by vacuum drying for 10-14 hours.
[0026] In some embodiments of the present invention, the Ni3(HITP)4 is prepared by the following method: after mixing HITP·6HCl and NiCl2·6H2O, NH3·H2O is added and reacted at 60-70°C for 2.5-3.5h to obtain the obtained product.
[0027] In some embodiments of the present invention, the molar ratio of HITP·6HCl to NiCl2·6H2O is (0.4-0.8):1.
[0028] In some embodiments of the present invention, NH3·H2O is added at 60-70°C.
[0029] According to a third aspect of the present invention, an application of the magnetic nanomaterial is provided, wherein the application is application as an adsorbent.
[0030] In some embodiments of the present invention, the application is application in plant hormone detection.
[0031] In some embodiments of the invention, the plant hormone comprises strigolactone.
[0032] In some embodiments of the invention, the strigolactones include GR24 and Strigol.
[0033] In some embodiments of the present invention, the application is application in the separation and determination of strigolactone enantiomers.
[0034] In some embodiments of the invention, the separation is a chiral separation.
[0035] In some embodiments of the present invention, the strigolactone enantiomers include (+)-GR24, (-)-GR24, (+)-strigol and (-)-strigol.
[0036] In some embodiments of the present invention, the application is application as a material for magnetic solid phase microextraction.
[0037] According to a fourth aspect of the present invention, a method for separating and determining the enantiomers of strigolactone is proposed, comprising the following steps:
[0038] S1, extracting the plant sample with acetonitrile, ultrasonicating, and performing solid-liquid separation to obtain an acetonitrile extract;
[0039] S2, adding the magnetic nanomaterial to the acetonitrile extract obtained in step S1 to perform solid phase microextraction, and then separating and collecting the magnetic nanomaterial;
[0040] S3, eluting the magnetic nanomaterial obtained in step S2, collecting the eluate; and analyzing the eluate by supercritical chromatography-mass spectrometry.
[0041] In some embodiments of the invention, the plant comprises Arabidopsis thaliana.
[0042] In some embodiments of the present invention, the mass volume ratio of the plant sample to acetonitrile is 100 mg: 0.5-1.5 mL.
[0043] In some embodiments of the present invention, the ultrasonication time is 5-15 min.
[0044] In some embodiments of the present invention, the solid-liquid separation is carried out by centrifugation, and the centrifugation time is 5-15 minutes.
[0045] In some embodiments of the present invention, the mass ratio of the magnetic nanomaterial to the plant sample is (1-10):100.
[0046] In some embodiments of the present invention, the mass ratio of the magnetic nanomaterial to the plant sample is (4-6):100.
[0047] In some embodiments of the present invention, the mass ratio of the magnetic nanomaterial to the plant sample is 5:100.
[0048] In some embodiments of the present invention, the solid phase microextraction time is 10-30 min.
[0049] In some embodiments of the present invention, the solid phase microextraction time is 25-30 min.
[0050] In some embodiments of the present invention, the solid phase microextraction time is 30 min.
[0051] In some embodiments of the present invention, the solid phase microextraction conditions are: shaking reaction at 2-6°C and 1000×g.
[0052] In some embodiments of the present invention, the method of separating and collecting the magnetic nanomaterials is to use a magnet for separation.
[0053] In some embodiments of the present invention, the solvent used for elution includes one of ethyl acetate, acetone and methanol.
[0054] In some embodiments of the present invention, the solvent used for elution is ethyl acetate.
[0055] In some embodiments of the present invention, the elution time is 10-30 min.
[0056] In some embodiments of the present invention, the elution time is 15-25 min.
[0057] In some embodiments of the present invention, the added mass volume ratio of the magnetic nanomaterial to the solvent used for elution is 1:(10-20).
[0058] In some embodiments of the present invention, the added mass volume ratio of the magnetic nanomaterial to the solvent used for elution is 1:10.
[0059] In some embodiments of the present invention, the volume of the solvent used for elution is 40 to 60 μL.
[0060] In some embodiments of the present invention, the instruments used in the supercritical chromatography-mass spectrometry technology include Nexera UC SFC and LCMS-8060NX mass spectrometer.
[0061] In some embodiments of the present invention, the chromatographic column used in the supercritical chromatography includes Chiralpak IA-3.
[0062] In some embodiments of the present invention, the analysis conditions of the supercritical chromatography are: compensation solvent: 0.1-0.3 mL / min methanol solution; mobile phase: mobile phase A is CO2, mobile phase B is methanol; flow rate: 1-2 mL / min; column temperature: 35-45°C; back pressure: 8-12 MPa; injection volume: 3-6 μL.
[0063] In some embodiments of the present invention, the analysis conditions of the supercritical chromatography are: compensation solvent: 0.2 mL / min methanol solution; mobile phase: mobile phase A is CO2, mobile phase B is methanol; flow rate: 1.5 mL / min; column temperature: 40°C; back pressure: 10 MPa; injection volume: 5 μL.
[0064] In some embodiments of the present invention, the elution method of the supercritical chromatography is isocratic elution.
[0065] In some embodiments of the present invention, the mass spectrometry conditions are: scanning mode: positive ion scanning; interface voltage is 4-5KV; focusing voltage is 1-3KV; heat block temperature is 380-420°C, and the temperature of the desolvation line is 230-270°C; drying gas flow rate is 4.5-5.5L / min; nebulizer gas flow rate is 1-2L / min; residence time is 80-120ms; MRM mode acquisition.
[0066] In some embodiments of the present invention, the mass spectrometry conditions are: scanning mode: positive ion scanning; the interface voltage in positive and negative ionization modes is 4.5KV; the focusing voltage is 2KV; the heat block temperature is 400°C, and the temperature of the desolvation line is 250°C; the drying gas flow rate is 5.0L / min; the nebulizer gas flow rate is 1.5L / min; the residence time is 100ms; and the MRM mode is collected.
[0067] In some embodiments of the present invention, the strigolactone enantiomers include (+)-GR24, (-)-GR24, (+)-strigol and (-)-strigol.
[0068] In some embodiments of the invention, the MRM parameters are as follows:
[0069]
[0070]
[0071] According to some embodiments of the present invention, at least the following beneficial effects are achieved: the magnetic nanomaterial Ni3(HITP)4@Fe3O4@rGO prepared by the scheme of the present invention can be used as an adsorbent for magnetic solid phase microextraction to purify and enrich GR24 and strigol isomers in plants, and can efficiently separate and determine SLs chiral isomers.
[0072] The method for analyzing and detecting chiral isomers of strigolactone using magnetic nanomaterial Ni3(HITP)4@Fe3O4@rGO has simple steps and can achieve chiral separation and high-sensitivity determination of chiral isomers of strigolactone. The detection limit can reach 1.93-3.76pg / mL, and the recovery rate is 86.90–106.37%. It can detect chiral isomers of strigolactone in trace samples. It has the advantages of being simple, rapid, highly sensitive, and environmentally friendly. It provides strong determination methodological support for in-depth analysis of cutting-edge fields such as SLs isomer signaling pathways and related regulatory mechanisms in plants. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0074] Figure 1 Schematic diagram of the synthesis of Ni3(HITP)4@Fe3O4@rGO nanomaterials and a schematic diagram of detection using Ni3(HITP)4@Fe3O4@rGO nanomaterials in Example 1 of the present invention, wherein (a) is a schematic diagram of the synthesis of Ni3(HITP)4@Fe3O4@rGO nanomaterials, and (b) is a schematic diagram of detection using Ni3(HITP)4@Fe3O4@rGO nanomaterials;
[0075] Figure 2 Graphs showing the characterization results of the Ni3(HITP)4@Fe3O4@rGO nanomaterials in Example 1 of the present invention, wherein a is an X-ray diffraction graph of rGO, Fe3O4@rGO and Ni3(HITP)4@Fe3O4@rGO, b is a graph showing the magnetic detection results of the Ni3(HITP)4@Fe3O4@rGO magnetic material measured by VSM, c is a graph showing the specific surface area analysis results of the Ni3(HITP)4@Fe3O4@rGO composite material, and d is a graph showing the FI-TR spectrum detection results;
[0076] Figure 3 The morphology results of scanning electron microscopy and transmission electron microscopy observations of rGO, Fe3O4@rGO, Ni3(HITP)4 and Ni3(HITP)4@Fe3O4@rGO graphene oxide in Example 1 of the present invention are shown, wherein a is the SEM image of rGO; b is the SEM image of Fe3O4@rGO; c is the SEM image of Ni3(HITP)4; d is the SEM image of Ni3(HITP)4@Fe3O4@rGO; e is the TEM image of rGO; f is the TEM image of Fe3O4@rGO; g and h are TEM images of Ni3(HITP)4@Fe3O4@rGO; i is the mapping image of Ni3(HITP)4@Fe3O4@rGO;
[0077] Figure 4 is a chromatogram of the strigolactone isomers in Example 2 of the present invention;
[0078] Figure 5 3 is a graph showing the optimization results of experimental factors in Example 3 of the present invention, wherein a is a graph showing the screening test results of magnetic solid phase microextraction materials; b is a graph showing the optimization results of magnetic solid phase microextraction dosage; c is a graph showing the optimization results of adsorption time; d is a graph showing the screening results of analytical agents; e is a graph showing the optimization results of analytical time; and f is a graph showing the optimization results of the volume of ethyl acetate as an analytical agent. DETAILED DESCRIPTION
[0079] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0080] Materials and Reagents:
[0081] (±)-strigol (>98%) and (±)-GR24 (>98%) were purchased from Olchemim, Czech Republic.
[0082] Methanol (>99.9%) and acetonitrile (>99.9%) were purchased from Merk, Germany.
[0083] Ethyl acetate (>99.9%) and acetone (>99.9%) were purchased from Tedia Company, USA.
[0084] 2,3,6,7,10,11-Hexamidinitibenzhexahydrochloride (HITP 6H2O) and nickel chloride hexahydrate (NiCl2·6H2O) were purchased from Shanghai MacLean Biochemical Co., Ltd.
[0085] Ammonia water (NH4OH, ≥25%), FeSO4 7H2O, FeCl3·6H2O, and rGO were purchased from Shanghai Aladdin Co., Ltd.
[0086] The standard solution (1000 mg / L) of each compound was prepared in acetonitrile and kept in a refrigerator at -20° C. All reagents were of analytical grade (purity above 98.0%).
[0087] Example 1
[0088] In this example, a magnetic nanomaterial Ni3(HITP)4@Fe3O4@rGO was prepared. The specific process is as follows: Figure 1 As shown, specifically:
[0089] (1) Preparation of Ni3(HITP)4 materials
[0090] Dissolve 3.538mmol HITP·6HCl and 5.469mmol NiCl2·6H2O in 10mL distilled water, and treat with ultrasound to form a uniform solution. Mix the solutions and place them in an oil bath and heat them to 65℃, then add 600μL NH3·H2O (14mol / L) to the above solution. Keep the reaction at 65℃ and stir continuously for 3h in air. After centrifugation, a black solid is obtained, which is the Ni3(HITP)4 material. After repeated washing with acetone and deionized water, vacuum dry at 150℃ for 12h, grind into powder and store dry.
[0091] (2) Preparation of Fe3O4@rGO materials:
[0092] 200 mg of graphene oxide was evenly dispersed in 50 mL of distilled water and ultrasonicated for 1 h. 3.64 g (0.04 mol) of FeCl3 6H2O and 1.80 g (0.02 mol) of FeSO4 7H2O were accurately weighed and dissolved in 25 mL of distilled water. At room temperature, with a nitrogen flow (flow rate of 40 mL / min) and rapid and vigorous stirring, the iron ion solution was slowly added to the graphene oxide solution and ultrasonically dispersed for 30 min. Subsequently, 5 mL of 25% ammonia solution was added, and the mixture was shaken in a water bath at 80 ° C for 2 h to obtain a black precipitate. The obtained black precipitate was repeatedly washed with deionized water and ethanol several times, and vacuum dried at 65 ° C for 12 h to obtain a Fe3O4@rGO nanocomposite material.
[0093] (3) Preparation of Ni3(HITP)4@Fe3O4@rGO materials:
[0094] 30 mg Ni3(HITP)4 powder was dispersed in 80 mL distilled water and ultrasonically treated for 60 min. Then 9 mL Fe3O4@rGO dispersion (6.667 mg / mL) was added and mixed for 30 min under stirring. The uniformly mixed Ni3(HITP)4@Fe3O4@rGO dispersion was filtered through a filter membrane under vacuum. The obtained solid phase material was then dried at 150 ° C under vacuum for 10 h, ground into powder, and stored dry.
[0095] (4) Characterization of Ni3(HITP)4@Fe3O4@rGO materials
[0096] 1) Structural characterization
[0097] Fourier transform infrared spectroscopy (FT-IR) was used to study the surface functional group structures of GO, Fe3O4@rGO and Ni3(HITP)4@Fe3O4@rGO. X-ray diffraction (XRD) was used to analyze the crystal properties of GO, Fe3O4@rGO and Ni3(HITP)4@Fe3O4@rGO. Vibrating sample magnetometer (VSM) was used to analyze the magnetism of Ni3(HITP)4@Fe3O4@rGO. Brunauer Emmett Teller (BET) provided the specific surface area value of Ni3(HITP)4@Fe3O4@rGO material. Element energy spectrum (mapping) was used to analyze the surface element composition of Ni3(HITP)4@Fe3O4@rGO.
[0098] The results are as follows Figure 2 As shown, from Figure 2 From the X-ray diffraction patterns of rGO, Fe3O4@rGO and Ni3(HITP)4@Fe3O4@rGO in Figure a, it can be seen that there are (002) and (001) crystal planes at 25.1° and 42.9° in the rGO pattern. The XRD pattern of Fe3O4@rGO is similar to the previous results. The peaks at 2θ of 30.3°, 35.7°, 43.3°, 53.6°, 57.2° and 62.9° are respectively consistent with the (220), (311), (400), (422), (511), (62.9) of the Fe3O4 crystal plane. (440) corresponds to the data of (JCPDS NO.19-0629), proving that Fe3O4@rGO has been successfully composited; in the XRD spectrum of Ni3(HITP)4@Fe3O4@rGO material, peaks can be clearly observed at 4.8°, 9.6° and 26.6°, corresponding to the (100), (200) and (001) crystal planes of Ni3(HITP)4MOF, respectively, indicating that Ni3(HITP)4MOF is successfully composited, and the characteristic peaks of Fe3O4@rGO exist at the same time, indicating that the target final material is successfully synthesized.
[0099] from Figure 2 As can be seen from Figure b, the magnetic properties of Ni3(HITP)4@Fe3O4@rGO magnetic material were measured by VSM at room temperature. The results showed that the hysteresis loop of the material was S-shaped, proving that the synthesized composite material has strong magnetism and the saturation magnetization intensity is 8.3emu / g.
[0100] from Figure 2As shown in Figure c, the specific surface area analysis of the Ni3(HITP)4@Fe3O4@rGO composite material shows that the specific surface area of the Ni3(HITP)4@Fe3O4@rGO material is 101.5 m 2 / g, indicating that Ni3(HITP)4 has a good surface area.
[0101] from Figure 2 From the FI-TR spectra of rGO, Fe3O4@rGO and Ni3(HITP)4@Fe3O4@rGO in Figure d, we can see that the OH stretching vibration peak of rGO is at 3442 cm -1 The characteristic absorption peaks of COC and C=O are at 1112 cm -1 and 1556cm -1 The spectrum analysis of Fe3O4@rGO composite material shows that the sample presents a relatively obvious Fe-O absorption peak specific to Fe3O4 (located at 575cm -1 ), also in this composite material, 3417cm -1 、1172cm -1 、1558cm -1 The characteristic peaks of rGO, OH stretching vibration peak, COC and C=O stretching vibration peak, are shown respectively, which further indicates that Fe3O4 is successfully loaded on the rGO surface. During the formation of Ni3(HITP)4, the conjugated π electrons of the ligand are redistributed to form a new higher conjugated system, resulting in the shift or change of the characteristic peaks of the CN bond and benzene ring compared with the ligand. Therefore, in the Ni3(HITP)4@Fe3O4@rGO material, the peaks related to the -NH and CN groups are shifted to 3433 and 1339 cm -1 The magnetic solid phase material after reloading Ni3(HITP)4 still has the absorption peak of Fe-O bond of Fe3O4 and the stretching vibration peak of C=O of rGO, indicating that the Ni3(HITP)4@Fe3O4@rGO material is successfully composited. The peak positions of the three curves overlap well, indicating that the structure of the composite material is consistent with expectations.
[0102] 2) Morphological characterization
[0103] The morphologies of rGO, Fe3O4@rGO, Ni3(HITP)4 and Ni3(HITP)4@Fe3O4@rGO graphene oxide were observed by scanning electron microscopy and transmission electron microscopy.
[0104] The results are as follows Figure 3 As shown, from Figure 3 From the SEM image in Figure a, we can see that rGO has a two-dimensional thin sheet structure with surface wrinkles, and from the TEM image, we can observe that rGO is in the form of thin sheets.
[0105] Through SEM images ( Figure 3 Figure b) and TEM ( Figure 3 Figure f) shows that it can be observed that the Fe3O4 nanoparticles in the Fe3O4@rGO composite are wrapped by the graphene oxide structure.
[0106] like Figure 3 As shown in Figure c, the SEM image shows that Ni3(HITP)4 consists of long columnar structures.
[0107] Through SEM images ( Figure 3 d figure in ) and TEM ( Figure 3 Figures e and h in the figure show that Fe3O4@rGO and Ni3(HITP)4 were successfully combined to form a composite material.
[0108] Figure 3 Figure g is the TEM image of Ni3(HITP)4@Fe3O4@rGO and its corresponding element mapping, from which it can be seen that the C, N, Ni and Fe elements are uniformly distributed in the composite material.
[0109] Example 2
[0110] This example provides a method for separating and detecting the corresponding isomers of strigolactone (+)-GR24, (-)-GR24, (+)-strigol and (-)-strigol in plants using the magnetic nanomaterial Ni3(HITP)4@Fe3O4@rGO prepared in Example 1. The structural formulas of the corresponding isomers (+)-GR24, (-)-GR24, (+)-strigol and (-)-strigol are as follows:
[0111]
[0112] The specific process is:
[0113] (1) Processing of plant samples:
[0114] Arabidopsis thaliana (Col-0) seeds were surface sterilized with 75% ethanol. After sterilization, the seeds were subjected to chromatography for 72 h in the dark at 4 °C to achieve synchronous germination. They were cultured in CK, 7 culture media containing a final concentration of 5 μmol / L (±)GR24, (±)strigol and its single chiral isomers (+)-GR24, (-)-GR24, (+)-strigol and (-)-strigol, respectively, and placed in a weak red light full sunlight environment at 22 °C. Each treatment was repeated three times, with 35 seeds per repeat.
[0115] After one week of cultivation, the treated Arabidopsis hypocotyls were photographed using a Canon 5-DS camera (45 Arabidopsis seedlings were randomly selected), and the hypocotyl length was measured using digimizer software. Under a microscope, the root hair length of the 7-day-old seedlings was measured. The root hair length was measured using Motic Images Plus software, with 10 photos processed each time (10 Arabidopsis seedlings were randomly selected), and 15 to 20 root hairs were measured in each photo. Statistical analysis of repeated means was performed according to IBM SPSS Statistics 27. The plant materials were ground into powder with liquid nitrogen and stored in an ultra-low temperature freezer at -80°C.
[0116] (2) Sample pretreatment:
[0117] Weigh 100 mg of Arabidopsis sample powder and transfer it to a centrifuge tube, add 20 μL of a 5 mg / L concentration of GR24 and strigol mixed standard solution to the sample powder, and immediately vortex to mix. Then add 1 mL of cold acetonitrile as the extract, centrifuge after ultrasonication for 10 minutes, and collect the upper extract. Add 5 mg of the Ni3(HITP)4@Fe3O4@rGO magnetic material prepared in Example 1 to the acetonitrile extract, and oscillate in a constant temperature oscillator at 4°C, 1000×g for 30 minutes. Use a magnet to quickly separate the magnetic solid phase microextraction material and the supernatant, discard the supernatant, and then add 50 μL of ethyl acetate, shake vigorously for 20 minutes, and elute SLs. Use a magnetic stand to quickly perform magnetic separation to obtain ethyl acetate eluent. Take 30 μL of supernatant and transfer it to an injection bottle with an inner tube. Collect the eluate and measure it by SFC-MS / MS. The general process of sample pretreatment is as follows Figure 1 As shown in Figure b.
[0118] (3) Supercritical fluid chromatography and mass spectrometry conditions
[0119] The SFC system was combined with a triple quadrupole mass spectrometer LCMS-8060NX. The specific configuration was CTO-20AC (column oven), LC-30AD (infusion pump), CBM-20A (system controller), DGU-20A5 (online degasser), LC-30ADSF (CO2 infusion pump), SFC-30A (back pressure regulating unit), LC-20AD (compensation pump), LCMS-8060NX (triple quadrupole mass spectrometer), SIL-30AC (autosampler), and LabSolutions Ver.5.91 (chromatographic workstation).
[0120] The SFC column is Chiralpak IA-3 (3.0 mm I.D. × 150 mm L., 3 μm). The mobile phase is delivered at a flow rate of 1.5 mL / min and consists of supercritical CO2 (A) and methanol (B). The compensation liquid is 0.2 mL / min methanol. The elution method used in the present invention is isocratic elution, and the initial concentration of phase B is 15%. The column temperature is 40°C and the injection volume is 5 μL. The pressure of the back pressure regulator is 10 MPa. The mass spectrometer system is operated in positive ion mode. The interface voltage in positive and negative ionization modes is 4.5 KV, and the focusing voltage is 2 KV. The temperatures of the heat block and the desolvation line are 400°C and 250°C, respectively. The flow rates of the drying gas and the nebulizer gas are set to 5.0 L / min and 1.5 L / min, respectively. The residence time is 100 ms. The multiple reaction monitoring mode (MRM) is used to acquire data, and the MRM detailed information of SLs is shown in Table 1. The TIC chromatogram of SLs is shown in Figure 4 shown.
[0121] Table 1
[0122]
[0123]
[0124] (4) Method validation
[0125] 1) Methodological validation
[0126] Blank samples were prepared in each set of samples, 15 samples in each set, and quality control samples including blank samples, spiked blank samples, and spiked matrix samples were evaluated. Continuous calibration verification standard solutions and continuous calibration blanks were used to verify SFC-MS / MS.
[0127] To validate the developed method, the linear range, precision, relative standard deviation (RSD), limit of quantification (LOQ), limit of detection (LOD) and matrix effect (ME) were investigated. Calibration curves were constructed for standards with concentrations of 0.2, 0.5, 1.0, 5, 10, and 50 μg / L for each analyte. The LOD value was 3 times the signal-to-noise ratio of the lowest spiked concentration sample, and the LOQ value was 10 times the signal-to-noise ratio of the lowest spiked concentration sample. To evaluate the accuracy of the method, the recovery of each analyte in quality control samples at three concentration levels of low (0.1 ng / g), medium (0.5 ng / g), and high (5.0 ng / g) was analyzed. The intra-day precision was evaluated by the relative standard deviation of the peak area by using three concentrations of 0.1 ng / g, 0.5 ng / g, and 5.0 ng / g for spiked recovery on the same day, and the inter-day precision was evaluated for 3 consecutive days. Each experiment was repeated 7 times. The matrix effect was calculated by comparing the response values of SLs spiked with pure solvent and pre-treated with the response values of SLs spiked with sample matrix and pre-treated. When ME is less than -20%, it indicates a strong matrix suppression effect; when ME is greater than 20%, it indicates a strong matrix enhancement effect; and when ME is between -20% and 20%, the matrix effect is not significant.
[0128] Data analysis: All data were analyzed and calculated using Microsoft Office Excel 2019, plotted using ORIGIN, and analyzed for significant differences in each group of data using SPSS18.0 (p < 0.05).
[0129] Table 2
[0130]
[0131]
[0132] The results are shown in Table 2. It can be seen from the table that each SLs stereoisomer has good linearity in the range of 0.2-50 μg / L (R 2>0.99). LODs and LOQs were 1.93-3.76pg / mL and 6.43-12.52pg / mL, respectively. The results showed that the online method was precise and accurate. At the same time, the extraction recovery and matrix effect of SLs stereoisomers ranged from 86.90-106.37% and 1.64-2.17%, respectively, with RSDs less than 20%. The matrix effects of each target were between 1.64% and 2.17%, indicating that the method can effectively reduce the matrix inhibition effect due to the use of matrix matching standard curves and solid phase materials.
[0133] 2) Methodological validation comparison
[0134] The method proposed in the scheme of the present invention was compared with the SLs analysis method reported in previous studies, and the results are shown in Table 3.
[0135] Table 3
[0136]
[0137]
[0138]
[0139] The method proposed in this study was compared with the SLs analysis method reported in previous studies. The results are shown in Table 3. The Ni3(HITP)4@Fe3O4@rGO composite material was used as an adsorbent for magnetic solid phase microextraction, and then combined with SFC-MS / MS for analysis, which significantly improved the detection sensitivity. The separation speed of SFC with supercritical fluid CO2 as the mobile phase is superior to that of traditional LC technology. The analysis time required for this method is only 5min, which is significantly lower than other reported methods, thereby further improving the analysis efficiency; and supercritical CO2 is safe and has no residue, which is more environmentally friendly than organic phase. In addition, the simple pretreatment method not only reduces the transfer loss, but also the method recovery rate reaches 86.90-106.37%, showing good stability and reliability. In summary, this method has the advantages of simplicity, rapidity, high sensitivity, and environmental friendliness, and provides a new and effective way for the analysis of SLs chiral isomers.
[0140] Example 3
[0141] This example optimizes the experimental method in Example 2. The specific optimization includes: using Ni3(HITP)4@Fe3O4@rGO magnetic material as an adsorbent for magnetic solid phase microextraction to enrich and purify SLs stereoisomers. To ensure the accuracy and reliability of the detection results, the optimization conditions of magnetic solid phase extraction were studied in depth, the types of magnetic composite materials were screened, and factors such as extraction time, elution time and eluent volume were optimized. The peak area of SLs stereoisomers was used as an indicator to examine the influence of various factors in magnetic solid phase microextraction.
[0142] (1) Screening of magnetic solid phase microextraction materials
[0143] The core of solid phase extraction lies in the performance of the adsorbent. By analyzing the special chemical structure of tricholoma lactone and comparing the adsorption effects of two magnetic composite materials, Fe3O4@rGO and Ni3(HITP)4@Fe3O4@rGO, on SLs, the best solid phase extraction material was screened out.
[0144] The detection method is referred to Example 2.
[0145] The results are as follows Figure 5 As shown in a in the figure, it can be seen that compared with Fe3O4@rGO magnetic material, the magnetic material composited with Ni3(HITP)4 has a better adsorption effect on SLs. Therefore, Ni3(HITP)4@Fe3O4@rGO is selected as the solid phase extractor of SLs.
[0146] (2) Optimization of magnetic solid phase microextraction dosage
[0147] By adding different amounts (1, 3, 4, 5, and 10 mg, respectively) of Ni3(HITP)4@Fe3O4@rGO material, the effects of different adsorbent doses in MSPE on the extraction efficiency of SLs were analyzed.
[0148] The detection method refers to Example 2, the only difference being the amount of Ni3(HITP)4@Fe3O4@rGO material added.
[0149] The results are as follows Figure 5 As shown in b, it can be seen from the figure that as the amount of Ni3(HITP)4@Fe3O4@rGO material added increases from 1 mg to 5 mg, the SLs extraction efficiency increases significantly. The increase in adsorption capacity can be attributed to the increase in the number of magnetic composite materials, resulting in a large number of adsorption sites available. When the amount of adsorbent exceeds 5 mg, there is no obvious increase in the corresponding area. Therefore, this experiment selected 5 mg of Ni3(HITP)4@Fe3O4@rGO material adsorbent for subsequent experiments.
[0150] (3) Optimization of adsorption time
[0151] In order to improve the extraction efficiency, the adsorption time should be shortened as much as possible while ensuring the best enrichment effect. Therefore, the experiment explored the effect of different adsorption times (0.5h, 1.0h, 1.5h and 2.0h) on the adsorption effect of SLs.
[0152] The detection method is similar to that of Example 2, the only difference being the adsorption time.
[0153] The results are as follows Figure 5 As shown in c, it can be seen from the figure that when the adsorption time is 0.5h, the extraction efficiency of SLs reaches the highest, and it basically does not increase when it exceeds 0.5h. As time goes on, the extraction efficiency of SLs stereoisomers decreases. It may be because the adsorption time is too long and the environmental factors are unstable, which leads to the degradation of plant hormones. In subsequent experiments, the adsorption time of 0.5h was selected.
[0154] (4) Screening of analytical agents
[0155] The type of desorbent has a direct impact on the recovery rate. In order to compare the efficiency of different desorbents, ethyl acetate, acetone and methanol were evaluated in this experiment.
[0156] The detection method is similar to that of Example 2, except that the type of analytical reagent is different.
[0157] The results are as follows Figure 5 As shown in Figure d, under the same experimental conditions, the desorption efficiency of ethyl acetate for SLs isomers is generally higher than that of methanol, and in most cases it is also better than acetone. In view of the desorption efficiency of ethyl acetate, ethyl acetate was selected as the desorbent in subsequent experiments.
[0158] (5) Optimization of parsing time
[0159] To ensure the best enrichment effect, the effects of different analysis times (10 min, 20 min and 30 min) on the extraction efficiency of SLs were studied.
[0160] The detection method is similar to that of Example 2, the only difference being the type of analysis time.
[0161] The results are as follows Figure 5 As shown in Figure e, when the desorption time is 20 min, the response value of SLs reaches a peak value and then tends to be stable, indicating that the desorption process of SLs has reached equilibrium. Therefore, 20 min is the optimal desorption time.
[0162] (6) Optimization of the volume of the analytical reagent
[0163] In order to increase the enrichment multiple and reduce the volume of the analytical agent as much as possible, the experiment investigated different volumes of analytical agents (50μL, 75μL and 100μL) to explore their specific effects on the extraction efficiency.
[0164] The detection method is similar to that of Example 2, except that the volume of analytical reagent added is different.
[0165] The results are as follows Figure 5 As shown in f, as the volume of the analytical agent increased from 50 μL to 100 μL, the analytical efficiency showed a downward trend due to the dilution effect of the analytical agent. Therefore, this paper selected an elution volume of 50 μL of analytical agent to optimize the extraction effect.
[0166] The present invention uses SFC-MS / MS to separate and detect SLs enantiomers in Arabidopsis samples. SFC uses CO2 as a mobile phase, has low viscosity and high diffusion characteristics, significantly improves separation efficiency and reduces separation time. In addition, CO2 is safe, non-toxic, green and environmentally friendly, and reduces costs and waste emissions. At present, the analysis and research of SLs are based on liquid chromatography combined with tandem mass spectrometry (LC-MS / MS) technology. However, the analysis method for SLs isomers still has certain limitations and needs further improvement and perfection. SFC-MS shows advantages that LC-MS / MS cannot match because of its extremely low organic solvent consumption and environmental friendliness. SFC has a fast analysis speed and can separate and analyze high-boiling point, low-volatile substances in a short time. It is also suitable for the preparation of chiral monomers. However, there is currently no relevant report on the use of SFC-MS / MS technology to separate SLs enantiomers.
[0167] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A magnetic nanomaterial, characterized in that: The magnetic nanomaterial is prepared by reacting Fe3O4@rGO and Ni3(HITP)4.
2. The magnetic nanomaterial according to claim 1, characterized in that: The mass ratio of the Fe3O4@rGO and Ni3(HITP)4 is 1:(1.5-2.5).
3. A method for preparing a magnetic nanomaterial according to any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: preparing by reacting Fe3O4@rGO and Ni3(HITP)4.
4. The method according to claim 3, characterized in that The Fe3O4@rGO is prepared by the following method: after reacting graphene oxide and an iron-containing metal salt, an alkaline solution is added, and the mixture is treated at 75-85° C. for 1-3 hours to obtain Fe3O4@rGO; Preferably, the iron-containing metal salt comprises ferric chloride and ferrous sulfate; Preferably, the mass ratio of the graphene oxide to the iron-containing metal salt is (30-40):1; Preferably, the reaction is carried out under the condition of introducing nitrogen, and the flow rate of the nitrogen is 30-50 mL / min.
5. The method according to claim 3, characterized in that: The Ni3(HITP)4 is prepared by the following method: HITP·6HCl and NiCl2·6H2O are mixed, and then NH3·H2O is added to react at 60-70°C for 2.5-3.5h to obtain the obtained product; Preferably, the molar ratio of HITP·6HCl to NiCl2·6H2O is (0.4-0.8):
1.
6. Use of the magnetic nanomaterial according to any one of claims 1 to 2 in any one of the following: (1) As an adsorbent; (2) Plant hormone detection; (3) Separation and determination of isomers of strigolactone; (4) As a material for magnetic solid phase microextraction; Preferably, the plant hormone comprises strigolactone; More preferably, the strigolactones include GR24 and Strigol; Preferably, the strigolactone enantiomers include (+)-GR24, (-)-GR24, (+)-strigol and (-)-strigol.
7. A method for separating and determining the isomers of strigolactone, characterized in that: The following steps are involved: S1, extracting the plant sample with acetonitrile, ultrasonicating, and performing solid-liquid separation to obtain an acetonitrile extract; S2, adding the magnetic nanomaterial according to any one of claims 1 to 2 to the acetonitrile extract obtained in step S1 to perform solid phase microextraction, and then separating and collecting the magnetic nanomaterial; S3, eluting the magnetic nanomaterial obtained in step S2, collecting the eluate; and analyzing the eluate by supercritical chromatography-mass spectrometry.
8. The separation and determination method according to claim 7, characterized in that The strigolactone enantiomers include (+)-GR24, (-)-GR24, (+)-strigol and (-)-strigol; and / or, the mass volume ratio of the plant sample to acetonitrile is 100 mg: 0.5-1.5 mL; and / or, the plant comprises Arabidopsis thaliana; and / or, the mass ratio of the magnetic nanomaterial to the plant sample is (1-10):100; And / or, the solid phase microextraction time is 10-30min; And / or, the solvent used for elution includes one of ethyl acetate, acetone and methanol; And / or, the elution time is 10-30 min.
9. The separation and determination method according to claim 7, characterized in that The chromatographic column used in the supercritical chromatography includes Chiralpak IA-3; And / or, the analysis conditions of the supercritical chromatography are: compensation solvent: 0.1-0.3 mL / min methanol solution; mobile phase: mobile phase A is CO2, mobile phase B is methanol; flow rate: 1-2 mL / min; column temperature: 35-45°C; back pressure: 8-12 MPa; injection volume: 3-6 μL; And / or, the mass spectrometry conditions are: scanning mode: positive ion scanning; interface voltage is 4-5KV; focusing voltage is 1-3KV; heat block temperature is 380-420°C, and the temperature of the desolvation line is 230-270°C; drying gas flow rate is 4.5-5.5L / min; nebulizer gas flow rate is 1-2L / min; residence time is 80-120ms; MRM mode acquisition.
10. The separation and determination method according to claim 9, characterized in that The MRM parameters are as follows: